Dome conditions in coastal city in tropical climate - Asmawan Mohd Sarman; Adi Irfan Che-Ani (2018)
The paper describes the long-term monitoring of the finishesperformance of the building with dome structure located in coastalarea. The theoretical proposal is based on relevant literature and wasapplied and adjusted in a survey of 24 buildings. Majority building inthe study is composed of mosque buildings and followed bygovernment buildings and business and office building. As the buildingmust also be in good condition to serve their purpose, there was concern about the effect ofthe outdoor factor on the durability of the building finishes. The main objective of themonitoring was to assess the effect of the environment in coastal area on the buildingfinishes. The study included the correlation between dome condition with age, coastaldistance, mean sea level height, material finishes and dome size. This paper explains themonitoring and results approach. The results indicated that the finishes use of variousbuilding materials has a different effect on the outer finishing conditions of the dome.Majority dome using concrete finish is in good condition compared to the dome that usesmetal sheet finish. This defect can be seen from the connecting part of the metal sheet panel.This is due to the incorrect or inaccurate installation method.